The Water Diviner and Other Stories - Vilhauer, Ruvanee Pietersz, 1962- (Book collections on Project MUSE., 2018)
In this thought-provoking collection, Sri Lankan immigrants grapple with events that challenge perspectives and alter lives. A volunteer faces memories of wartime violence when she meets a cantankerous old lady on a Meals on Wheels route. A lonely widow obsessed with an impending apocalypse meets an oddly inspiring man. A maidservant challenges class divisions when she becomes an American professor's wife. An angry tenant fights suspicion when her landlord is burgled. Hardened inmates challenge a young jail psychiatrist's competence. A father wonders whether to expose his young son's bully at a basketball game. A student facing poverty courts a benefactor. And in the depths of an isolated Wyoming winter, a woman tries to resist a con artist. These and other tales explore the immigrant experience with a piercing authenticity.